THU0107 Prevalence of Positive Quantiferon-Gold Test in Adult Patients with Active Rheumatoid Arthritis and Its Significance in Developing Countries - Cama, R.; Manaktala, C. (Annals of the rheumatic diseases, 2016)
BackgroundThe detection of latent TB infection (LTBI) and institution of appropriate prophylactic therapy is an essential requirement before prescribing biologic disease modifying anti-rheumatic drugs (DMARDs) to patients with rheumatoid arthritis. With several biologics going off-patent and a mushrooming of biosimilars, biologics which were hitherto unaffordable and unavailable in the developing world are soon likely to be widely available. In view of the high prevalence of active tuberculosis (TB) and LTBI in these regions, the increased prescribing of biologics will raise some pertinent questions in the context of LTBI testing, test result interpretation and management.ObjectivesThe objective of this study was to identify the prevalence of latent TB infection in a geographically diverse population of patients with Rheumatoid Arthritis eligible for treatment with biologic DMARDs.MethodsA retrospective analysis of QuantiFERON-TB Gold (QFT-G) test results of samples received at Quintiles Central Laboratories from Jan 2010 to Dec 2013 was conducted. All samples were from adult subjects who were consented and screened for clinical trials. All subjects had active Rheumatoid arthritis of at least 6-month duration as per ACR 1987 criteria and had inadequate response to conventional DMARDs including MTX therapy.ResultsThe QFT-G test results of 4471 samples were analyzed. Samples were received from 40 countries with 66% from Europe, 18% from USA and Canada, 18% from APAC region and 5% from Latin America.The total incidence of positive QFT-G in this sample size was 12.3% with range of positivity extending from 2.4% in Canada to 37.8% in China. Romania, Korea, Bosnia and Mexico also had significant QFTG positivity of 31.5%, 30.2%, 28.7% and 20.3% respectively. The total incidence of indeterminate results to QFT-G test was 5.2%.The Asian countries predictably showed a higher prevalence of LTBI, with 25.2% of test results being positive. Eastern Europe and Latin America followed with 13.1% and 11.5%, while Western Europe had 8.2% and USA & Canada had only 4.5% positive QFT-G test resultsConclusionsWith increasing availability of biologics in regions with high tuberculosis disease burden there appears to be a requirement to develop country-specific guidelines for prophylaxis of latent TB tailored to the needs of the populace. In terms of duration of prophylaxis, will the recommended 6-month INH prophylactic regimen be adequate to effectively prevent re-activation of TB in the developing countries? As patients with Rheumatoid Arthritis continue to take biologic DMARDs for longer durations of time, will a life-long preventive strategy be necessary? There is also concern for presence of INH resistance in these regions, effectively bringing into play more toxic prophylactic regimens for prevention of tuberculosis. National guidelines for patient pathways and selection of biologic may be the required solution to enable patients of rheumatoid arthritis to avail of better therapies while avoiding potential risks.ReferencesWorld Health Organization. Global Tuberculosis Report 2013Centres of Disease Control and Prevention: Updated Guidelines for Using Interferon Gamma Release Assays to Detect Mycobacterium tuberculosis InfectionDisclosure of InterestNone declared